Simplified Material Solution for Orthotropic Symmetrical GFRP Laminates for Structural Facades - Yuchao Zhao; Xu Jiang; Qilin Zhang; Xuhong Qiang (Advances in Civil Engineering)
GFRP (glass-fiber-reinforced polymer), as a composite material, possesses many favorable properties including high strength and low weight and is amenable to unique processing methods; therefore, it is a potential free-form surface material. However, the complex design theory owing to anisotropy limits its application. Thus, a simplified material solution becomes significant. In this study, the strength and stiffness of orthotropic symmetrical GFRP laminates are derived theoretically, and a simplified material solution is proposed to simplify the anisotropy as isotropy. Then, using the numerical simulation of an actual orthotropic symmetrical GFRP laminate free-form facade structure, the effectiveness of the simplified material solution is analyzed and evaluated. This solution can provide guidance for similar GFRP facades and further promote the application of GFRP in engineering.